Effects of injection strategy on performance and emissions metrics in a diesel/methane dual-fuel single-cylinder compression ignition engine. (December 2019) - Korkmaz, Metin; Ritter, Dennis; Jochim, Bernhard; Beeckmann, Joachim; Abel, Dirk; Pitsch, Heinz
In order to counteract the drawbacks of conventional diesel combustion, which can lead to high indicated specific nitric oxide and indicated specific particulate matter emissions, a promising diesel-dual-fuel concept is investigated and evaluated. In this study, methane is used as supplement to liquid diesel fuel due to its benefits like high knock resistance and clean combustion. A deep understanding of the in-cylinder process is required for engine design and combustion controller development. To investigate the impact of different input parameters such as injection duration, injection timing, and substitution rate on varying output parameters like load, combustion phasing, and engine-out emissions, numerous investigations were conducted. Engine speed, global equivalence ratio, and injection pressure were held constant. The experiments were carried out in a modified single-cylinder compression ignition engine. The results reveal regimes with different dependencies between injection timing of diesel fuel and combustion phasing. This work demonstrates the potential of the diesel-dual-fuel concept by combining sophisticated combustion control with the favorable combustion mode. Without employing exhaust gas recirculation, TIER IMO 3 emissions limits are met while ensuring high thermal efficiency.